On nonlinear dynamic system arising in Potts model - Ganikhodjaev, Nasir; Nawi, Mohamed Ashraf (Faculty of Science, Faculty of Biosciences and Faculty of Bioengineering UTM Skudai, with Faculty of Science and Technology, Universitas Airlangga, Indonesia, 2011)
From three-state Potts model we produce the recursion relations that provide us numerically exact phase diagrams of the Potts model. Each phase is characterized by a pafticular attractor and the phase diagram is obtained by following the evolution and detecting the qualitative changements of these attractors. Ihese changements can either be continuous or abrupt, respectively,characterizing second or first order transitions. We present a few typical attractors.